The rare Adisianus Bretfeld (Collembola, Bourletiellidae): a new species from Northeastern Brazil and an identification key to the genus - Rodrigues, Iandra Vitória Bezerra; Medeiros, Gleyce Da Silva; Nunes, Rudy Camilo; Bellini, Bruno Cavalcante (Zootaxa, 2025)
Bourletiellidae (Symphypleona, Appendiciphora, Sminthuroidea) comprises several genera exclusively distributed across tropical and subtropical regions worldwide. Adisianus Bretfeld, a genus within this family, is found in the Neotropical Region and currently includes only three species described from forested areas in Brazil and Mexico. Here we revisit the genus describing a new species, Adisianus pinheadi sp. nov., from a transitional area between the Cerrado and Caatinga biomes in the Northeastern region of Brazil. The new species is more similar to A. fuscus (Bretfeld) and A. maculatus (Bretfeld) in the presence of rough blunt spine-like chaetae on antennae, dorsal head and large abdomen, but it is unique in the combination of its color pattern, antennal and head chaetotaxy, and number of chaetae on manubrium and tenaculum. We also update the diagnosis of the genus, provide an identification key to its species, and discuss its similarities with the Sphyrothecinae (Sminthuridae), along with the potential implications for the internal relationships within Symphypleona.